MODERASI ISLAM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Hidayat, Tatang; Abdussalam, Aam; Istianah, Istianah (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
The purpose of this study is to describe the moderation of Islam in the study of Islamic religious education. This research uses a qualitative approach and a literature study method. Based on the results of the study, Islamic teachings are radical in the sense that all of their teachings and practices are rooted in a solid belief system. The more radical the understanding and practice of religion, the softer and more it guarantees good for all. Al-Qur'an expresses Islamic moderation in the language of "actual" ummata wasatha as evidence of a strong guarantee of his teachings. In the development of learning, Islamic moderation can lower the principles of tasyamul, takamul, tawazun, tasamuh, tarahum and tahabub. The principle of tasyamul and takamul builds a comprehensive and integrative perspective on all entities and gives birth to the paradigm of tawhid. The principles of tawazun and tasamuh will develop an instructional system capable of balancing empirical and spiritual truths and viewing differences as wealth. The principle of tarahum and tahabub will be able to develop educational communication based on compassion and love so that educators can capture students' hearts and present to be a center of self-identification.